The Influence of Examiner Gender on Responses to Tonic Heat Pain Assessments: A Preliminary Investigation - McDougall, Jessica F.; Bailey, Nicole G. N.; Banga, Rohan; Linde, Lukas D.; Kramer, John L. K. (Frontiers in Pain Research, 2021)
Background: The influence of examiner gender on pain reporting has been previously explored in both research and clinical settings. However, previous investigations have been limited, with the majority of studies employing single, static assessments of pain (e.g., cold pressor test, verbal pain ratings). The impact of examiner gender on both static and dynamic heat-based pain assessments is currently unknown. Methods: Thirty eight participants (20 females aged 24.1 ± 4.44, and 18 males, aged 24.8 ± 4.54) completed two identical testing sessions, randomized to a male and female examiner in a cross-over design. Pain sensitivity was examined using heat pain thresholds, verbal pain ratings to tonic heat, computerized visual analog scale (CoVAS) rating to tonic heat, and participant-controlled temperature (PCT) heat pain assessments. Results: Female participants reported higher verbal pain to tonic heat with a female examiner compared to male participants, with similar trends for CoVAS responses to tonic heat. Conversely heat pain thresholds and PCT were not significantly influenced by experimenter gender. Conclusions: Overall, verbal ratings were the most impacted by examiner gender, with temperature-based methods such as PCT and pain thresholds showing little to no examiner gender effects. While the gender of the examiner may be an important consideration in the measurement of sex and gender differences in pain research, the choice of pain assessment method may be of similar consequence.